EFFECT OF SUPLEMENTATION (AMINO ACID, MINERALS, AND VITAMINS) THROUGH DRINK WATER AGAINST QUALITY OF EGG SAVED UP TO 21 DAYS. - I P. L., Sastrawan; Astawa, I P. A.; Mahardika, I G. (Jurnal Peternakan Tropika, 2020)
This study was conducted to determine the effect of supplementation (amino acids, minerals, and vitamins) through drinking water on the quality of eggs stored for 21 days and was carried out in Candikusuma Village, Melaya District, Jembrana Regency, Bali Province for 4 months. This study used a completely randomized design (CRD) with 3 treatments (P0, P1, and P2) and 5 replications, the number of eggs used was 90 eggs. Variables observed were egg weight, egg specific gravity, yolk index, egg yolk color, and haugh egg unit. The results showed that the percentage of decreased egg quality stored for up to 21 days given supplementation (amino acids, minerals, and vitamins) through drinking water 0,05% and 0,1% were statistically significantly different (P>0,05) on the index egg yolk compared to control. The percentage decrease in egg quality given supplementation (amino acids, minerals, and vitamins) through drinking water 0,05% and 0,1% statistically showed significant differences (P<0,05) on egg weight, egg specific gravity, color egg yolks, HU eggs compared to controls. Based on the results of the study concluded that supplementation (amino acids, minerals, and vitamins) through drinking water can maintain the quality of eggs stored for up to 21 days.  Keywords:eggs, supplementation, egg quality